The Anti-Cancer Effect of Mangifera indica L. Peel Extract is Associated to γH2AX-mediated Apoptosis in Colon Cancer Cells - Marianna Lauricella; Valentina Lo Galbo; Cesare Cernigliaro; Antonella Maggio; Antonio Palumbo Piccionello; Giuseppe Calvaruso; Daniela Carlisi; Sonia Emanuele; Michela Giuliano; Antonella D'Anneo (MDPI AG, 2019)
Ethanolic extracts from Mangifera indica L. have been proved to possess anti-tumor properties in many cancer systems. However, although most effects have been demonstrated with fruit pulp extract, the underlying molecular mechanisms of mango peel are still unclear. This study was designed to explore the effects of mango peel extract (MPE) on colon cancer cell lines. MPE affected cell viability and inhibited the colony formation trend of tumor cells, while no effects were observed in human dermal fibroblasts used as a non-cancerous cell line model. These events were a consequence of the induction of apoptosis associated to reactive oxygen species (ROS) production, activation of players of the oxidative response such as JNK and ERK1/2, and the increase in Nrf2 and manganese superoxide dismutase (MnSOD). Significantly, mango peel-activated stress triggered a DNA damage response evidenced by the precocious phosphorylation of histone 2AX (γH2AX), as well as phosphorylated Ataxia telangiectasia-mutated (ATM) kinase and p53 upregulation. Mango peel extract was also characterized, and HPLC/MS (High Performance Liquid Chromatography/Mass Spectrometry) analysis unveiled the presence of some phenolic compounds that could be responsible for the anti-cancer effects. Collectively, these findings point out the importance of the genotoxic stress signaling pathway mediated by γH2AX in targeting colon tumor cells to apoptosis.